2015
DOI: 10.1136/gutjnl-2015-309521
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of lipase activity in chronic pancreatitis: Table 1

Abstract: We read with great interest the article by Weiss et al 1 reporting genetic associations of rs632111 (fucosyltransferase 2; FUT2), rs8176693 (ABO) and rs889512 (chymotrypsinogen B2; CTRB2) with lipase levels. Weiss et al also claimed that the variants at the FUT2 and ABO loci were associated with chronic pancreatitis (CP). No association with CP was observed for the CTRB2 locus. Elevated lipase levels are a diagnostic criterion for acute pancreatitis and might mirror subclinical pancreatic injury in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…61 Interestingly, the CEL protein carries blood group antigens and a GWAS in 2015 indicated that fucosyl-transferase 2 nonsecretor status and blood group B are risk factors for CP. 62 Although other studies in ethnically mixed cohorts failed to replicate this association, 63,64 with the exception of azathioprine-induced pancreatitis in patients with inflammatory bowel disease, 65 it is still interesting to speculate that the observed effects might have been due to changes in CEL folding or trafficking.…”
Section: Mis-folding-associated Cel Mutations and Cel-hyb Allelementioning
confidence: 99%
“…61 Interestingly, the CEL protein carries blood group antigens and a GWAS in 2015 indicated that fucosyl-transferase 2 nonsecretor status and blood group B are risk factors for CP. 62 Although other studies in ethnically mixed cohorts failed to replicate this association, 63,64 with the exception of azathioprine-induced pancreatitis in patients with inflammatory bowel disease, 65 it is still interesting to speculate that the observed effects might have been due to changes in CEL folding or trafficking.…”
Section: Mis-folding-associated Cel Mutations and Cel-hyb Allelementioning
confidence: 99%
“…Also for chronic pancreatitis, a study has reported that ABO blood group status, in particular the B phenotype, is a risk factor for this inflammatory condition (60,61). However, others have found no association between ABO blood groups and chronic pancreatitis (62,63). Moreover, FUT2-negative status has been linked to chronic pancreatitis (60, 61) but not to pancreatic cancer (31,32), and it is an open question whether the inactivation of the FUT2 gene product represents a detrimental or beneficial effect with regard to human health.…”
Section: Carboxyl-ester Lipase Contains Abo Blood Group Determinantsmentioning
confidence: 99%
“…Blood group antigens attached to the surface of the CEL protein and fucosyltransferase 2 (FUT2) non-secretor status (which affects the status of the ABO antigens, especially blood group B) was associated in a genomewide association study (GWAS) [37]. However, in following studies, this association could not be confirmed apart from an association between blood group B and azathioprine-induced AP [38][39][40].…”
Section: Carboxyl Ester Lipase (Cel-hypb1 Allele)mentioning
confidence: 98%